Screening of aquatic plant for potential phytoremediation of heavy metal contaminated water - Wan Mohd Musdek, Wan Noraina Atikah (2015)
Bioremediation is a new green economic approach in providing solutions for cleaning up contaminated sites. Phytoremediation is a branch of bioremediation that uses plants as a tool for remediation purposes. The mass amount of contaminants especially heavy metals is a worrying concern to the mass public in recent times. The usage of phytoremediation using plant species offers higher potential solution to remediate heavy metal contaminated sites. This study intended on screening potential plant species for phytoremediation of heavy metal contaminated water. The potential of three aquatic macrophytes species (Eichorrnia crassipes, Pistia stratiotes and Ipomoea aquatica) to be used for chromium and nickel phytoremediation was tested. The plants were exposed for ten days under hydroponic conditions to the designated heavy metals contaminated water in order to assess the suitability of the aquatic plants to remediate the water. The E. crassipes showed the highest chromium and nickel concentration detected in plant biomass, 1.60 μg/L and 2.40 μg/L, respectively. Meanwhile, P. stratiotes of chromium and nickel concentrations detected were 0.89 μg/L and 0.081 μg/L, respectively; chromium and nickel concentration of I. aquatica detected were, 0.49 μg/L and 0.080 μg/L, respectively. The ability of these plants to accumulate metals and survived throughout the experiment demonstrates the potential of these plants to remediate metal enriched water. Among the three tested aquatic plants, E. crassipes showed the most suitable plant species that can phytoremediate heavy metal contaminated water followed by P. stratiotes and I. aquatica.